Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/healthcare8020129
|View full text |Cite
|
Sign up to set email alerts
|

Is Belonging to a Religious Organization Enough? Differences in Religious Affiliation Versus Self-Ratings of Spirituality on Behavioral and Psychological Variables in Individuals with Heart Failure

Abstract: In the United States, heart failure (HF) affects approximately 6.5 million adults. While studies show that individuals with HF often suffer from adverse symptoms such as depression and anxiety, studies also show that these symptoms can be at least partially offset by the presence of spiritual wellbeing. In a sample of 327 men and women with AHA/ACC classification Stage B HF, we found that more spirituality in patients was associated with better clinically-related symptoms such as depressed mood and anxiety, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 63 publications
(99 reference statements)
2
13
0
1
Order By: Relevance
“…This finding is in line with a study that explored potential factors affecting anxiety in Spain, in which the authors found that participants with a high score for spirituality had a 0.320-fold lower level of anxiety [33]. Current studies also found that spirituality was correlated with anxiety [62,63]. Spirituality is, indeed, generally helpful for people dealing with major life stressors, as positive psychological concepts including an individual's core values, deep connections, orientation, and beliefs relate to physical and mental health [64,65].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in line with a study that explored potential factors affecting anxiety in Spain, in which the authors found that participants with a high score for spirituality had a 0.320-fold lower level of anxiety [33]. Current studies also found that spirituality was correlated with anxiety [62,63]. Spirituality is, indeed, generally helpful for people dealing with major life stressors, as positive psychological concepts including an individual's core values, deep connections, orientation, and beliefs relate to physical and mental health [64,65].…”
Section: Discussionsupporting
confidence: 89%
“…Concerning regression models, and in coherence with other studies in different clinical settings, spiritual well-being emerged as the most relevant protective factor for depression, anxiety and PSTD (Krupski et al, 2006;Saiz et al, 2020). Loneliness was the next main predictor for the three dependent variables.…”
Section: Discussionsupporting
confidence: 80%
“…According to Ellison ( 43 ), moreover, spiritual well-being includes both a psycho-social dimension and a more religious dimension, a unifying force that aims to integrate the physical, emotional and social dimensions of health. A study by Saiz et al ( 44 ) demonstrated that spirituality in people with heart failure has broader associations with measures of psychosocial and physical symptoms than belonging to a religious organization and that religious affiliation alone did not emerge as a reliable predictor for health benefits. Indeed, it was even counterproductive: in fact they found that those who belonged to a religious organization, but with a low level of spirituality, perceived a state of anxiety and greater emotional fatigue.…”
Section: Spiritual Wellbeing and Mental Healthmentioning
confidence: 99%